2008
DOI: 10.1160/th07-06-0424
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent roles for heparin in modifying liopolysaccharide-induced activation of mononuclear cells in whole blood

Abstract: In addition to their anticoagulant activity, unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH) have important immunomodulatory properties. However, different studies have reported conflicting pro- and anti-inflammatory effects in association with heparin. Moreover, the molecular basis for these heparin effects on inflammation remains unclear. It was the objective of this study to determine how UFH and LMWH regulate lipopolysaccharide (LPS)-induced activation of human mononuclear cells in who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
5
25
0
Order By: Relevance
“…Some studies have reported lower levels of LPS binding protein (LBP; a soluble acute-phase protein produced by liver in response to infection that binds LPS and markedly enhances its affinity for the TLR4 complex) in cord blood than in adult blood (33,44); however, this observation was not reproduced in another study (45). Lower levels of LBP or other soluble factors in cord blood are unlikely to be a dominant factor, since other authors have shown that LPS can active monocytes under serum-free conditions (46,47). Indeed, a study by Kato and colleagues showed that, in human peripheral blood mononuclear cells (PBMCs), only the interferon regulatory transcription factor 3 (IRF-3)-inducible genes (but not the NF-B-inducible genes that include the TNF-␣ gene) are strictly LBP dependent upon LPS stimulation (48).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported lower levels of LPS binding protein (LBP; a soluble acute-phase protein produced by liver in response to infection that binds LPS and markedly enhances its affinity for the TLR4 complex) in cord blood than in adult blood (33,44); however, this observation was not reproduced in another study (45). Lower levels of LBP or other soluble factors in cord blood are unlikely to be a dominant factor, since other authors have shown that LPS can active monocytes under serum-free conditions (46,47). Indeed, a study by Kato and colleagues showed that, in human peripheral blood mononuclear cells (PBMCs), only the interferon regulatory transcription factor 3 (IRF-3)-inducible genes (but not the NF-B-inducible genes that include the TNF-␣ gene) are strictly LBP dependent upon LPS stimulation (48).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that heparin may inhibit the production of cytokines from human monocytes (17,19).…”
Section: Methodsmentioning
confidence: 96%
“…Preincubation with soluble heparin and chondroitin sulphate has previously been shown to dampen the inflammatory response in cells stimulated with IL-1β, correlated with reduced NF-κB signalling, but the mechanisms of action by the polysaccharides are not clear (Hochart et al, 2006;Jomphe et. al., 2008;Legendre et al, 2008).…”
Section: ø Arlov Et Al Biomimetic Sulphated Alginate Hydrogelsmentioning
confidence: 99%
“…A r t i c u l a r c a r t i l a g e i s r i c h i n s u l p h a t e d glycosaminoglycans (GAGs) which have significant roles in hydration, cell motility and intra-and intercellular communication, and are thus of great interest for incorporation in tissue engineering scaffolds (Chen et al, 2007;Pieper et al, 2000). Heparin, in particular, has been shown to have anti-inflammatory effects by reducing nuclear translocation of NF-κB, thus lowering expression of inflammatory cytokines, and may further inhibit downstream processes by direct association with cytokines, adhesion proteins and the complement and coagulation cascades (Hochart et al, 2006;Parish, 2006;Spillmann et al, 1998;Weiler et al, 1992).…”
Section: Introductionmentioning
confidence: 99%